Relationship between Birch Pollen Counts and Meteorological Factors for 8 years in Sapporo - Narita, Shin-ichirou; Asakura, Kohji; Shirasaki, Hideaki; Yamamoto, Tetsuo; Watanabe, Kazumasa; Kanaizumi, Etsuko; Ogasawara, Hideki; Konno, Nobuhiro; Kataura, Akikatsu; Satoh, Jun; Himi, Tetsuo (Nippon Jibi Inkoka Gakkai Kaiho, 2003)
Occurrence of airborne pollen in Sapporo was studied for the 8 years between 1995 and 2002. Observations on pollen seasons of cedar. birch, grass, and mugwort are presented. There are wide year-to-year variations in quantities of birch pollens. Simple linear regression by the least squares method was used for studying correlations between annual quantities of birch pollen and the meteorological factors. A highly significant (P=0.00004) positive correlation was found between precipitation in February of the preceding year and annual birch pollen concentrations with the coefficient of determination. R2=0.950. These results suggest that atmospheric birch pollen counts can be predicted from the meteorological factor in the preceding year.